Conceptual modeling of database object-oriented applied to soil studies – DATASOLOS_SC (Revista de Ciências Agroveterinárias, 2024)
Information systems are able to store important data so as that these can be consulted and analyzed for the most varied uses and applications.  The way how the data is stored in a database makes it easy the organization, query and update of information. The conceptual modeling has been successfully applied in the building of databases enabling represent in an abstract way, formal and unambiguous, the reality of application. The objective of this study was to design a structure of a database by means of conceptual modeling for applications in the field of soil science through of OMT model, aimed the organizing, systematizing, and managing of the information available about this natural resource, through a relational object database management system. The DATASOLOS_SC gathers general, physical, chemical and morphological data of soil profiles from Santa Catarina State – Brazil, besides a soil samples library (physical bank). The initial version of the soil database will be available for access at the electronic address https://datasolos-sc.sistemas.udesc.br/.
Keywords: database; object orientation; soils